2016
DOI: 10.1186/s12887-016-0586-x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary miRNA profiles identify children with autism spectrum disorder, correlate with adaptive behavior, and implicate ASD candidate genes involved in neurodevelopment

Abstract: BackgroundAutism spectrum disorder (ASD) is a common neurodevelopmental disorder that lacks adequate screening tools, often delaying diagnosis and therapeutic interventions. Despite a substantial genetic component, no single gene variant accounts for >1 % of ASD incidence. Epigenetic mechanisms that include microRNAs (miRNAs) may contribute to the ASD phenotype by altering networks of neurodevelopmental genes. The extracellular availability of miRNAs allows for painless, noninvasive collection from biofluids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 30 publications
5
104
0
1
Order By: Relevance
“…A succession of ensuing studies reported widespread miRNA dysregulation in the CNS and periphery, including lymphoblasts (911), blood (1214), saliva (15), and olfactory precursor cells (16). These studies have produced vast amounts of information, some unifying and some conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A succession of ensuing studies reported widespread miRNA dysregulation in the CNS and periphery, including lymphoblasts (911), blood (1214), saliva (15), and olfactory precursor cells (16). These studies have produced vast amounts of information, some unifying and some conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Four of these studies involved brain tissue (8, 5254), three involved peripheral blood (1214), one examined saliva (15), one examined olfactory precursor cells (16), and three employed cultured lymphoblasts (911). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Frank Middleton and colleagues used the salivary microRNA profiles for identification of children with ASD [53]. Here, we present the first systematic evaluation of HKGs in the salivary transcriptome to be used for normalization of RT-qPCR data in ASD research.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, while RNA molecules in the cell tend to be short-lived, circulating microRNAs show much higher stability and are protected from degradation by endogenous RNases [14]. Altered levels of specific microRNAs in body fluids have been linked to a wide range of diseases, including disorders of the nervous system [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Serum microRNA levels were altered in children with autism spectrum disorders and salivary levels have been correlated with neurodevelopmental scores [15,16].…”
Section: Introductionmentioning
confidence: 99%